Prevalence of Post-traumatic Stress Disorder Status Among Healthcare Workers and Its Impact on Their Mental Health During the Crisis of COVID-19: A Cross-Sectional Study - Yang, Yue; Liu, Di; Liu, Bingshuo; Ou, Weiyan; Wang, Licheng; Ma, Yuanshuo; Fan, Lihua; Shi, Yu; Shi, Lei (Frontiers in Public Health, 2022)
Objective: After the unprecedented coronavirus disease 2019 (COVID-19) outbreak, the health status of the general population has suffered a huge threat, and the mental health of front-line healthcare providers has also encountered great challenges. Therefore, this study aims to: 1) investigate the prevalence and influencing factors of post-traumatic stress disorder (PTSD) among healthcare providers, and 2) verify the moderating role of self-efficacy in the influence of PTSD on mental health. Methods: A cross-sectional study was conducted using an online survey of 1993 participants. The presence of depression, anxiety, self-efficacy, and PTSD was evaluated using screening tests from March 1. Sociodemographic and COVID-19-related data were also collected. A data analysis was performed using descriptive statistics, Pearson’s correlation coefficient, and multiple linear regression. Results: The prevalence of PTSD among healthcare providers was 9.3%. PTSD was negatively correlated with self-efficacy (r= -0.265, P< 0.01), anxiety (r= -0.453, P< 0.01), and depression (r= 0.708, P< 0.01). Profession, daily working hours, maximum continuous working days, and daily sleep time were influencing factors of PTSD. A binary logistic regression analysis showed that physicians (OR = 2.254, 95% CI = 1.298, 3.914) and nurses (OR = 2.176, 95% CI = 1.337, 3.541) were more likely to experience PTSD than other healthcare providers. Conclusion: Self-efficacy has a moderating effect on the influence of PTSD on anxiety and depression. This suggests that health managers need to respond to the current psychological crisis of healthcare providers, implement appropriate psychological interventions, and minimize the psychological harm caused by COVID-19.